School Culture in Instilling Religious Character of Madrasah Tsanawiyah - Suriadi Suriadi (Program Studi Pendidikan Agama Islam, 2020)
This article discusses the culture of instilling religious character. This research was conducted at Madrasah Tsanawiyah Muhammadiyah Sejangkung Sambas Regency. This research was focused on (1) curriculum, (2) student development, (3) educators and education staff management. The research approach used was qualitative. The analysis results show that (1) the curriculum used nationally refers to Ministry of Religion which is then developed with the students' learning development needs, (2) student coaching to develop their religious character through the habituation method by instilling religious values, discipline, and honesty, and ( 3) related to the management of educators and education staff, Tsanawiyah Madrasah carried out training programs, workshops, teacher meeting. These activities are efforts of madrasah to increase the educators and education staff knowledge and competencies.